Law and the Epistemology of Disagreements - Alex Stein (Washington University Law Review, 2018)
This Article identifies a discrepancy between law and epistemology and proposes a way to fix it. Our legal system relies on decisions of multimember tribunals, which include juries, state and federal appellate courts, and supreme courts. Members of those tribunals often disagree with each other on matters of fact. The system settles such disagreement by applying head-counting rules: the unanimity or supermajority requirement for jury verdicts and the majority rule for judges’ decisions. Under these rules, jurors can return an agreed-upon verdict even when their reasons for supporting the verdict are inconsistent with one another. Similarly, judges are authorized to deliver any decision so long as it is supported by a majority of the panel. Disagreements among judges and jurors are consequently ironed out instead of being accounted for as a factor that reduces the reliability of the final decision. By adopting these rules, our legal system allows jurors to convict the defendant when six of them believe the incriminating account provided by one witness, while rejecting as non-credible the testimony of another prosecution witness, and the remaining six jurors form a diametrically opposite view of the two witnesses’ credibility. Moreover, the system authorizes appellate courts to determine by a narrow 2-1 majority that a violation of the accused’s constitutional trial right was “harmless beyond a reasonable doubt.” Likewise, it accords the status of an unreservedly binding precedent to a 5–4 decision of the United States Supreme Court that determines the meaning of a statutory or constitutional provision. These rules are fundamentally incompatible with the epistemological principles of rational fact-finding. The epistemology of disagreement maintains that when a person makes a factual finding and then realizes that an equally informed, competent, and honest individual—an “epistemic peer”—arrived at a different conclusion, based on the same information, she ought to scale down her level of confidence in her own opinion. A peer’s disagreement is evidence writ large that a person cannot rationally ignore or discount. Rather, it must be given weight and cause one to revisit her original opinion. This epistemological principle has far-reaching implications for the law. For example, a guilty verdict rendered by a jury cannot be considered unanimous when the underlying reasons contradict each other; a dissent by a single appellate judge should preclude a guilty sentence under the “beyond a reasonable doubt” standard; and a precedent laid down by a narrow majority of the Supreme Court should remain open to reconsideration.
Keywords: epistemology; multimember tribunals; disagreements; epistemic peer; legal theory; bottom line rule; hung jury rule; non-unanimous decisions